2014
DOI: 10.21071/az.v63i241.592
|View full text |Cite
|
Sign up to set email alerts
|

Grasa y proteína de la leche de vaca: componentes, síntesis y modificación

Abstract: El objetivo de este trabajo fue realizar una revisión de los componentes lipídicos y proteicos de la leche de vaca, ya que los ácidos grasos, las caseínas, y las proteínas del lactosuero, entre otros, poseen una importancia significativa dentro de la nutrición humana. En este ámbito, el consumidor elige entre uno u otro componente, influyendo de manera directa sobre la oferta y la demanda de productos lácteos. Esta dependencia del mercado hacia el consumidor, exige al profesionista involucrado en la producción… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 78 publications
0
9
0
15
Order By: Relevance
“…Such variations may be attributable in the prepartum period to a high level of body reserves and absence of milk synthesis, conditions that allow to the animal to face the delivery and initiation of production; however, lowering serum triglyceride level arising subsequently, reflects the energy deficit which is exposed the cow and as a normal process, it takes the necessary energy from the oxidation of triglycerides that has reserved in adipose tissue, which has in its structural conformation, glycerol, and triglycerides (Duque et al, 2011). From day 45 postpartum, it was observed that levels rose, as the cow stabilizes its energy status and the triglycerides increase to be transported in chylomicrons and in very low-density lipoprotein, to mammary gland, to synthesize preformed fatty acids (palmitic and stearic) (García et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Such variations may be attributable in the prepartum period to a high level of body reserves and absence of milk synthesis, conditions that allow to the animal to face the delivery and initiation of production; however, lowering serum triglyceride level arising subsequently, reflects the energy deficit which is exposed the cow and as a normal process, it takes the necessary energy from the oxidation of triglycerides that has reserved in adipose tissue, which has in its structural conformation, glycerol, and triglycerides (Duque et al, 2011). From day 45 postpartum, it was observed that levels rose, as the cow stabilizes its energy status and the triglycerides increase to be transported in chylomicrons and in very low-density lipoprotein, to mammary gland, to synthesize preformed fatty acids (palmitic and stearic) (García et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, other articles found values of 0.67 and 0.7 kg of protein (13,14) , values close to those found in the present investigation. Various authors state that the protein concentration of milk does not present outstanding changes with nutritional manipulation (19) . However, the effect of soybean meal on nitrogen use and protein production in Holstein cows has been evaluated, reaching conclusions that milk and protein yield do not show an increase with a supplementation level of soybean meal higher than 16.5 %.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate investigation, the author suggested that knowledge of genetic variability could be useful when altering the composition of milk protein, since the estimation of the genetic parameters of the six main milk proteins determined by capillary electrophoresis in zone are highly related (21) . According to García et al (19) , this information suggests the possibility of modifying the protein composition of cow's milk through selective breeding, which in turn offers the opportunity to satisfy the new consumer demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, el metilpalmitato mostró un comportamiento similar a lo que indica la literatura (25%), ya que estuvo en concentración de 27.9% (suplementadas) y 24.81% (no suplementadas). Las diferencias encontradas se indica que corresponden a diferencias metabólicas ruminales asociadas con los diferentes tipos de dietas (García et al, 2014).…”
Section: Discussionunclassified